Petrographic and chemical analysis of pottery: the case of prehistoric pottery from Passavas, Laconia - Πολυγένη, Νικολέττα (Πανεπιστήμιο Πελοποννήσου, 2020)
Archaeometric approaches in archaeology are becoming increasingly popular. Pottery studies are enhanced by archaeometric interpretations offering more integrated approaches. In the present study 14 pottery samples from southern Laconia dated macroscopically and archaeologically to the transitional phase of Middle to Late Helladic period are petrographically and chemically investigated. Cultural dynamics during the emergence of the Mycenaean civilization and their impact in pottery traditions are widely discussed. The pottery from Passavas in southern Laconia, is distinguished by the influence of Minoan traditions, posing exciting questions about the origin, manufacture and traditions of its ceramic techniques and styles. The analytical methods of optical petrography and scanning electron microscopy are used to investigate issues of provenance and technology. The results of the petrographic analysis indicate a high correlation with the geology of the area and practices of pottery manufacture applied in the wider area of southern Laconia, including Kythera. Pastes of clay established for Kythera are also encountered in Passavas. The results of the chemical analysis are indicative of the metamorphic geological character of the area of Passavas or Kythera, in contrast to the sedimentary geological character of Ayios Stephanos, a well-known site in proximity, despite the high correlation of the latter with Passavas, regarding pottery traditions and styles.
Keywords: Πετρολογία στην αρχαιολογία; Κεραμική, Προϊστορική -- Ελλάδα -- Λακωνία -- Ανάλυση; Κεραμική, Ελληνική -- Ελλάδα -- Λακωνία -- Ανάλυση; Κεραμική, Προϊστορική -- Ελλάδα -- Λακωνία -- Σύνθεση; Κεραμική, Ελληνική -- Ελλάδα -- Λακωνία -- Σύνθεση; Κεραμικά -- Ανάλυση; Λακωνία (Ελλάδα) -- Αρχαιότητες; Πασσαβάς (Λακωνίας, Ελλάδα) -- Αρχαιότητες; Πετρογραφία κεραμικής; Ηλεκτρονικό μικροσκόπιο σάρωσης; Χημική ανάλυση; Προϊστορική κεραμική; Μινωίζουσα κεραμική; Πρώιμη Μυκηναϊκή εποχή; Λακωνία; Πασσαβάς; Thin section microscopy; Petrography; SEM; Chemical analysis; Prehistoric pottery; Early Mycenaean; Minoanization; Shaft grave era; Southern Laconia; Passavas